Limitaciones al reconocimiento del territorio ancestral en Ecuador (Tema Central) - Galindo Lozano, Andrea Soledad (2020)
As of the 2008 Constitution, Ecuador recognized ancestral territory as a collective right of indigenous communities, peoples and nationalities for constituting a space for the preservation of culture. This right that could also be considered a manifestation of the intercultural state has been limited since the executive’s speech and through normative provisions. This research addresses the study of the right to ancestral territory and the limitations it has suffered in Ecuador. To demonstrate this premise, one of the emblematic cases on the boundaries of ancestral territory will be analyzed, it is about the Nankints community belonging to the Shuar people, based on two approaches: the international one, based on the jurisprudence of the Inter-American Court of Human Rights, the American Convention on Human Rights and the ILO Convention 169 on Indigenous and Tribal Peoples; and that of the intercultural State since the revision of the Ecuadorian Constitution through the norms that have been issued on the subject. The objective of this investigation is to show that the limitations to the law of the ancestral territory do not respond to a theoretical-normative analysis only, in many cases they are the product of the political will of the government of the day.